Ali Smith’s Girl Meets Boy: Exploration of Homosexuality - Ramesh Prasad Adhikary (Journal La Sociale, 2020)
The present research paper is the extensive analyses of Ali Smith’s seminal novel Girl Meets Boy by applying Queer Theory as a tool. As a qualitative research, this paper is the study of queer behavior of characters of the fiction which questions over the established heterosexual social conceptions. The authoritative concept of heterosexual bond has been challenged with the idea of queerness or homosexual bond. The character Anthea and Robin cross the social life of heterosexuality and got the freedom physically and sexually in their lesbian love. As revolutionary characters, they question over the dominant narrative of heterosexuality and create a new test for readers. This fiction portrays the myth of sexual minorities in a new way. Their sexual behavior portrays shifting notion of sexuality because of awareness of gender biasness. It also proves that the identity is cultural construct and the characters have created distinct identity going against the so called socially established sexual behaviours.